THE RESULTS OF LONG-TERM STUDY OF HERPESVIRUS INFECTION AT THE DEPARTMENT OF INFECTIOUS DISEASES IN CHILDREN OF RUSSIAN NATIONAL RESEARCH MEDICAL UNIVERSITY - O. V. Shamsheva; F. S. Kharlamova; N. Yu. Egorova; O. V. Molochkova; E. V. Novosad; E. V. Simonova; T. M. Lebedeva; N. A. Guseva (Детские инфекции (Москва))
As a result of many years of research, the role of Herpesviridae IV, V and VI types in the structure of various pathologies in children (with infectious mononucleosis (MI), CNS damage, long-term subfebrile syndrome, vasculitis syndrome, hepatitis, etc.) has been proven. MI is a polyethological disease associated with the Epstein-Barr virus (EBV), cytomegalovirus (CMV) and human herpesvirus type 6 (HHV6), occurring in mono(58%) and mixed infections in various combinations of herpesviruses (42%). Clinical manifestations of MI are typical and do not depend on etiology. With CMV and HHV6 IM, the response to heterophilic antibodies is always negative. Markers of herpesvirus infections were detected in 87% of children observed with neurological pathology. Children with diagnoses such as convulsive syndrome, epilepsy, neuropathy need a comprehensive examination (ELISA, PCR, Indirect immunofluorescence reaction) to identify markers of active replication of herpes viruses, with an emphasis on the detection of HHV6. In 44% of cases, the role of active herpesvirus infection in the etiology of prolonged subfebrile fever in children was proven, with mixed forms (78%) prevailing over monoinfection (22%). To identify the active forms of herpesvirus infection, it is important to detect the markers of viral replication. For EBV, this is the DNA of the virus in the blood, a smear from the tonsils and saliva, antigens of the complete assembly of EBV in blood lymphocytes, antibodies to the capsid antigen (VCA) of IgM and IgG classes, and IgG to the early (EA) antigen. With CMV infection, complete virus assembly antigens (pp65 and pp72) in blood lymphocytes and/or DNA of the virus in the blood, virus DNA in saliva and urine, antibodies to the IgM class virus and high IgG class titer in the blood. With HHV6 infection, the DNA of the virus in the blood, a smear from tonsils and saliva, complete antigens of HHV6 in blood lymphocytes, specific IgM and/or IgG antibodies are 2—4 times higher than the diagnostic values.